Pyrolytic coproduction of biochar and upgraded biooils from abundant agroindustrial wastes - Casoni, Andrés Iván (2021)
The co-production of bio-char and upgraded bio-oil by fast pyrolysis of raw and sulfuric-acid pretreated agro-industrial wastes (corn cob, sugarcane bagasse and sunfower seed hull) was investigated to valorize wastes as sources of value-added products (VAPs) following the circular bio-economy system. To this end, proximate and elemental analyses were performed, and adsorption properties were determined in pyrolysis products. Bio-char and bio-oil yields from raw wastes ranged 28?33% and 30?35%, respectively. For all wastes, acid pretreatment increased the solid fraction and caused a reduction of the liquid one, compared to untreated wastes. Pyrolysis of raw wastes led to the co-production of bio-chars and bio-oils with diferent applications. Bio-chars could be put in for soil amendment, primarily due to high ashes concentration, mesoporosity, andelevated cation exchange capacity; whereas, bio-oils could be upgraded by water addition, leading to a source for carrying out reforming reactions in the context of hydrogen production. Properties of bio-chars from acid washed biomasses enabled them for pollutant remediation, due to their high specifc surface and microporosity features. The corresponding bio-liquid was a stable-to-storage material, being a practical source of furfural. These fndings emphasize that lignocellulosic wastescan be envisaged as starting materials for producing VAPs via pyrolysis.